1995
DOI: 10.1111/j.1365-2621.1995.tb06203.x
|View full text |Cite
|
Sign up to set email alerts
|

Modified Atmosphere‐packed Marinated Chicken Breast and Rainbow Trout Quality as Affected by Package Leakage

Abstract: Marinated chicken breast pieces and sliced rainbow trout were packed in modified atmosphere and stored to measure effects of package leakage. The sensory shelf life of products decreased slowly but linearly as leakage rate increased, with exception of the appearance of sliced rainbow trout, which was not affected by leakage rate. The concentration of ethanol in head space was a potential indicator of spoilage and package leakage for both nroducts. The nresence of dimethvlsulfide indicated spoilage of chicken f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 14 publications
1
14
1
1
Order By: Relevance
“…The pork loin slices were used for psychrotrophic aerobic count, the block portions were used for pH determination, and the films in the bottom of Petri dishes were used for colorimetric analysis. Two additional by microorganisms, which break down food carbohydrates, proteins, and fats to a wide variety of low-molecular-weight molecules (RANDELL et al, 1995;MATTILA;TAWAST;AHVENAINEN, 1990).…”
Section: Experimental Designmentioning
confidence: 99%
“…The pork loin slices were used for psychrotrophic aerobic count, the block portions were used for pH determination, and the films in the bottom of Petri dishes were used for colorimetric analysis. Two additional by microorganisms, which break down food carbohydrates, proteins, and fats to a wide variety of low-molecular-weight molecules (RANDELL et al, 1995;MATTILA;TAWAST;AHVENAINEN, 1990).…”
Section: Experimental Designmentioning
confidence: 99%
“…Randell et al [1995] reported an increase in the ethanol concentration of anaerobically MA packaged marinated chicken as a function of storage time. The Lawrence Berkeley National Laboratory has developed a sensing material for the detection of Escherichia coli 0157 enterotoxin [Cheng & Stevens, 1998].…”
Section: Intelligent Packaging Systemsmentioning
confidence: 99%
“…Randell et al (1995) reported an increase in the ethanol concentration of anaerobically MA packaged marinated chicken as a function of storage time.…”
Section: Magnifiedmentioning
confidence: 99%
“…visual or optochemical) to a package holds promise as a means of ensuring package integrity through the distribution chain. A number of studies on package integrity in MAP meat products (Eilamo et al, 1995;Randell et al, 1995;Ahvenainen et al, 1997;Smolander et al, 1997) have established critical leak sizes and associated quality deterioration. Standard (destructive) manual methods for package integrity and leak testing are both laborious and can test only limited numbers of packs (Hurme, 2003).…”
Section: Integrity Indicatorsmentioning
confidence: 99%